PENILAIAN KINERJA FISIK (MATERI) KOPERASI SYARI’AH MENURUT PERSPEKTIF SHARI’ATE ENTERPRISE THEORY DENGAN NILAI TAMBAH SYARI’AH DAN ZAKAT SEBAGAI INDIKATOR - Handayani Soedarso, Elvyra (Program Studi Akuntansi FPEB UPI, 2013)
The results of the assessment on the performance of sharia cooperatives are strongly influenced by the analytical tools used. Analyzes that have been there only focused on a mere financial perspective with the meaning of finances limited to property or material. Whereas should the assessment of Sharia cooperative performance should be more comprehensive and comprehensive considering the role and function of Shari'ah cooperative which is not only limited to profit oriented but also non profit oriented. Assessment of Shari'ah cooperative performance according to shari'ate enterprise theory perspective assesses the performance of three forms of reality: physical reality, psychic reality and spiritual reality. Performance appraisal of physical reality is viewed from the perspective of financial piety, mental and social reality seen from the perspective of mental and social piety and spiritual reality seen from the perspective of spiritual piety. In this study, the discussion is limited only to the assessment of the physical performance of Shari'ah cooperatives by using the added value of Shariah and Zakat as an indicator of its assessment. The results showed that Sharia Added Value as the first indicator used to assess the physical performance of Shari'ah cooperatives assessed performance based on economic added value, mental added value and spiritual added value. While zakat as the second indicator of physical performance of Shari'ah cooperative is the transformation from the achievement of net profit to the achievement of zalcat, by using the object of zakat appraisal that is optimum.